Participatory building and analysis of multiple set of scenarios - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
At Centro American arena level, this inovation has been used by SECAC for EASAC formulation. In Costa Rica, it has been used by MINAE in NDC 2017 and its revision in 2020 (NDC 2020). In other countries, has been used to discuss various initiatives and plans.